Epileptiform activity in the acute phase of stroke predicts the outcomes in patients without seizures - Lasek-Bal, Anetta; Dewerenda-Sikora, Milena; Binek, Łukasz; Student, Sebastian; Łabuz-Roszak, Beata; Krzystanek, Ewa; Kaczmarczyk, Aleksandra; Krzan, Aleksandra; Żak, Amadeusz; Cieślik, Aleksandra; Bosak, Magdalena (Frontiers in Neurology, 2023)
Abstract Background and purpose The abnormalities in EEG of stroke-patients increase the risk of epilepsy but their significancy for poststroke outcome is unclear. This presented study was aimed at determining the prevalence and nature of changes in EEG recordings from the stroke hemisphere and from the contralateral hemisphere. Another objective was to determine the significance of abnormalities in EEG in the first days of stroke for the post-stroke functional status on the acute and chronic phase of disease. Methods In all qualified stroke-patients, EEG was performed during the first 3 days of hospitalization and at discharge. The correlation between EEG abnormalities both in the stroke hemisphere and in the collateral hemisphere with the neurological and functional state in various time points was performed. Results 131 patients were enrolled to this study. 58 patients (44.27%) had abnormal EEG. The sporadic discharges and generalized rhythmic delta activity were the most common abnormalities in the EEG. The neurological status on the first day and the absence of changes in the EEG in the hemisphere without stroke were the independent factors for good neurological state (0-2 mRS) at discharge. The age-based analysis model (OR 0.981 CI 95% 0.959-1.001, p=0.047), neurological status on day 1 (OR 0.884 CI 95% 0.82-0.942, p<0.0001) and EEG recording above the healthy hemisphere (OR 0.607 CI 95% 0.37-0.917, p=0.028) had the highest prognostic value in terms of achieving good status 90 days after stroke. Conclusions Abnormalities in EEG without clinical manifestation are present in 40% of patients with acute stroke. Changes in EEG in acute stroke are associated with a poor neurological status in the first days and poor functional status in the chronic period of stroke.